In Situ Formation of Metal-Ceramic Microstructures by Partial Reduction Reactions in the Ni-Ai-O System: Principles, Properties and Issues - E. Üstiindag; P. Ret; R. Subramanian; R. Dieckmann; S. L. Sass (The Minerals, Metals and Materials Society, 1994)
"Partial reduction reactions in the Ni-AI-O system, starting with the spinel compound NiAI20 4, are used to form metal-ceramic microstructures. By suitable choice of processing parameters, such as reduction temperature, oxygen partial pressure and time, two different morphologies of nearly pure Ni particles, equiaxed and rod-like, form within a ceramic matrix, which is either a-A12O3 or a metastable ""defect spinel"". Electron microscopy studies were performed for microstructural characterization, phase identification and chemical analysis. The fracture toughness of the Ni-AI2O 3 mixture was significantly improved with respect to that of the original spinel phase. The important issues that must be addressed to form useful metal-ceramic microstructures by partial reduction reactions rue discussed. It is shown that cracking at the original spinel grain boundaries, likely due to the large volume changes associated with the reduction reaction, can be avoided by the addition of small amounts of ZrO2• Initial results illustrating effect of ZrO2 on the microsuuctures are presented.IntroductionEngineering materials used in load bearing circumstances, particularly under extreme conditions (e.g. high temperatures or stresses), generally are formulated with complex microsuuctures. Such composite-like materials can possess properties unobtainable by either of the individual constituents. With metal-ceramic composites, for example, a material can be obtained with an optimum combination of the low density and high strength of the ceramic, and the toughness of the metal. For high temperature service, where demanding conditions are often present, for example, inside jet turbine engines, a successful new material must have low density, high Young's modulus as well as good oxidation resistance, strength, fracture toughness, creep and fatigue resistance. The candidates include intermetallic compounds, and metal-ceramic, intermetallic-ceramic and ceramic-ceramic composites."